INDUSTRY 4.0 AND IT’S INFLUENCE TOWARDS REORIENTATION OF INTERNATIONAL TRADE BEHAVIOUR - Ashar, Javier (Universitas Muhammadiyah Yogyakarta, 2020)
From the beginning until today, The Industrial World has experienced at least 3 revolutions. The first revolution occurred in 1784 in England marked by the mechanization of production. The second revolution occurred in the late 19th century until the 1970s with the use of electric-powered machines for mass production activities, while the third revolution occurred after the 1970s until now which is characterized by the use of computer / digital technology for automation of production activities. First introduced at The Hanover Fair in Germany, the term Industry 4.0 was intended to represent the concept of the fourth Industrial Revolution. Like the Industrial Revolution in previous eras, the fourth Industrial Revolution marked by digitizing production equipment and its integration with the internet is predicted to provide many opportunities for benefits as well as potential risks for anyone involved in it. Some of the results of previous studies have explored the definitions, characteristics of the fourth Industrial Revolution compared to the previous Industrial Revolution along with changes in the orientation of the State in its trade activity policies with other countries within the framework of Industry 4.0. Therefore, this article aims to examine how Industry 4.0 along with its various characteristics can influence the pattern of trade activities between countries. The analysis in this article will use the liberal-capitalist economic approach and the concept of free markets in the hope of providing an overview of how the fourth Industrial Revolution can influence the pattern of trade activities between countries. Keywords: Industry 4.0; influence; trade between countries